ACCEPTANCE AND USE OF STAINLESS STEEL CROWNS AMONG DENTAL STUDENTS IN VIETNAM: A TECHNOLOGY ACCEPTANCE MODEL PERSPECTIVE (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the level of acceptance and identify factors associated with the intention and actual use of stainless steel crowns among dental students based on the technology acceptance model.Subject and methods: A cross-sectional descriptive study was conducted among 372 dental students from 10 dental training institutions in Vietnam. A 16-item questionnaire was used to evaluate five constructs: perceived usefulness, perceived ease of use, attitude, behavioral intention, and actual use.Results: Students reported high perceived usefulness of stainless steel crowns (80.2 ± 15.5%) and strong behavioral intention to use them (80.9 ± 14.4%). However, perceived ease of use (54.3 ± 22.0%) and actual clinical use (49.2 ± 22.8%) remained limited. The overall acceptance score was 66.5 ± 12.2%, predominantly at a moderate level. Acceptance levels differed significantly across training institutions (p = 0.046). In regression analysis, behavioral intention showed the strongest association with actual use (β = 0.19; p < 0.001), and the model explained 46% of the variance in actual use.Conclusion: Despite high intention to use stainless steel crowns, actual clinical practice remains limited; therefore, enhanced supervised clinical exposure is warranted to bridge the gap between intention and behavior.
Keywords: Stainless steel crowns, technology acceptance model, dental students, behavioral intention, actual usage.